Pengaruh Latihan Variasi terhadap Ketepatan Servis Atas pada Siswa yang Mengikuti Ekstrakurikuler Bola Voli Putra di SMA Negeri 3 Bangko Pusako Kabupaten Rokan Hilir - Indra Kurniawan; Ardiah Juita; Aref Vai (Journal on Education, 2023)
Bangko Pusako 3 Public High School students who take part in the men's volleyball extracurricular are the subject of this study, and the purpose of this study is to find out how variations of training affect the accuracy of the upper serve. This research was conducted in November and December 2022. Twelve students who took part in the men's volleyball extracurricular made up the population of this study. The total sampling method was used to select a sample of 12 students for research. AAHPER Service Accuracy is an instrument used to collect data. To determine the category of explanation of training variations on the accuracy of men's volleyball serve, the data were analyzed descriptively and inferentially. Using SPSS 25.0 statistics, the inferential analysis method uses three tests, namely the normality test with the Liliefors test, the homogeneity test with the Levene test, and the hypothesis test with the t test by comparing the mean between the pretest and posttest using the percentage increase. With and a significance level of , it can be concluded that the upper serve variation exercise has a significant effect on the accuracy of men's volleyball serves from the research that has been described.